Kesalahan Umum dalam Penarikan Kesimpulan: Kajian Literatur Penalaran Induktif, Deduktif, Modus Ponens dan Modus Tollens - Prihaten Maskhuliah; Salwa Rifdah Rizqullah; Sarmila Sarmila (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
The ability to reason is inherent in humans as rational beings and forms the basis for constructing knowledge and solving everyday problems. Logical thinking enables individuals to express ideas, build valid arguments, and make informed decisions. However, errors in drawing conclusions often occur due to insufficient understanding of systematic reasoning rules. This article aims to explain methods of drawing conclusions based on mathematical logic, including inductive reasoning, deductive reasoning, Modus Ponens, and Modus Tollens, while also discussing common formal reasoning errors. Using a library research method, the discussion focuses on the characteristics, practical applications, and validity of each reasoning method through logical truth tables. The analysis shows that deductive reasoning provides certain conclusions when valid premises are used, whereas inductive reasoning generates general conclusions based on probability derived from empirical observations. The study also identifies common logical fallacies, including affirming the consequent and denying the antecedent, which undermine argument validity. Understanding formal mathematical logic is expected to strengthen critical thinking, support valid argument construction, and help readers avoid reasoning errors in academic writing and everyday decision-making.